Between control and complexity: opportunities and challenges for marine mesocosms. Issue 7 (September 2016) - Sagarin, Raphael D; Adams, John; Blanchette, Carol A; Brusca, Richard C; Chorover, Jon; Cole, Julia E; Micheli, Fiorenza; Munguia‐Vega, Adrian; Rochman, Chelsea M; Bonine, Kevin; van Haren, Joost; Troch, Peter A
Abstract : Marine ecologists have a wide array of tools with which to study complex and dynamic systems, but there are cases where neither simple, highly controlled experiments nor largely uncontrolled, more complex field observations provide adequate inferential power. In such cases, mesocosm studies in marine systems may help bridge the gap. Mesocosm studies can facilitate research ranging from basic biology to multifactorial ecosystem studies that involve observation, perturbation, validation, calibration, long‐term studies, and testing of new technologies. Although scale, closed boundaries, biodiversity levels, and replication can impose challenges on mesocosm research, these parameters can also help to define research opportunities that are uniquely suited to such controlled environments. Finally, we provide examples of successful marine mesocosm research and discuss opportunities for future work.